Implementasi SIKADES Berbasis Web untuk Mempermudah Layanan Administrasi Desa - Fikri; M. Fuaddunnazmi; Haryanto, Edy; Indriaturrahmi (Infotek: Jurnal Informatika dan Teknologi, 2025)
Information technology has become a very important tool in improving the efficiency and effectiveness of administrative processes in various organizations, both in the public and private sectors. This study aims to design a web-based population information system and village data administration (SIKADES) using Visual Studio Code and to test the feasibility of the Web. This study uses the Waterfall development method which is one of the methods in the Software Development Live Cycle (SDLC). The development stages include requirement analysis, design, development, and testing. There are 2 instruments used in the study. Observation sheets were given to 2 validators to test the reliability of SIKADES and the feasibility test questionnaire was given to 27 village officials to test user responses to the effectiveness of SIKADES. The results obtained in this study are: (1) The score of all reliability indicators has an average of 4.2 indicating that SIKADES is feasible to use and (2) The score of all effectiveness questionnaire indicators has an average of 4.4 indicating that SIKADES is effective (3) The average user satisfaction score from several indicators is 75% -78% with a category of satisfied to use. Another finding in this study is that SIKADES security still needs to be improved.